Effects of bacteriophage on Salmonella Enteritidis infection in broilers - Zahra Sarrami; Mohammad Sedghi; Ishmael Mohammadi; Mike Bedford; Hadi Miranzadeh; Razie Ghasemi (Scientific Reports, 2023)
Abstract Bacteriophages (BP) are viruses that can infect bacteria. The present study evaluated the effect of BP on Salmonella infected broilers. A number of 150 day-old broilers were used in a completely randomized design with five treatments that included: (1) basal diet from day 0 to 28; (2) basal diet + 0.3 g/kg of colistin from day 0 to 28; (3) basal diet from day 1 to 13, and basal diet + 0.4 g/kg of colistin from day 14 to 28; (4) basal diet + 1 g/kg of BP from day 0 to 28; (5) basal diet + 1.5 g/kg of BP from day 0 to 28. On day 13, 15 chickens from each treatment were challenged by Salmonella Enteritidis (SE), while fifteen from each treatment were not; instead, they were kept in the same cage with the challenged chickens (exposed chickens). At 7 and 14 days post-challenge, the number of SE and coliform bacteria in the cecum and liver of colistin and BP-fed birds was lower than the control treatment. In exposed and challenged chickens, the height and surface area of villus were greater in the BP and colistin-supplemented groups. Serum concentrations of aspartate aminotransferase and alanine transaminase were greater, while serum albumin and triglycerides concentrations were lower in the control treatment. The liver of the challenged chickens had more pathological lesions than exposed birds. BP significantly decreased PPARγ gene expression in exposed chickens. In the challenged and exposed chickens, TLR4 gene expression was lower in BP and colistin-treated birds as compared to the control. In conclusion, adding BP to the diet from the day of age prevents the spread of Salmonella.